Solve for y 3*(-6y)=63

Math
3⋅(-6y)=63
Multiply -6 by 3.
-18⋅y=63
Divide each term by -18 and simplify.
Tap for more steps…
Divide each term in -18⋅y=63 by -18.
-18⋅y-18=63-18
Cancel the common factor of -18.
Tap for more steps…
Cancel the common factor.
-18⋅y-18=63-18
Divide y by 1.
y=63-18
y=63-18
Simplify 63-18.
Tap for more steps…
Cancel the common factor of 63 and -18.
Tap for more steps…
Factor 9 out of 63.
y=9(7)-18
Cancel the common factors.
Tap for more steps…
Factor 9 out of -18.
y=9⋅79⋅-2
Cancel the common factor.
y=9⋅79⋅-2
Rewrite the expression.
y=7-2
y=7-2
y=7-2
Move the negative in front of the fraction.
y=-72
y=-72
y=-72
The result can be shown in multiple forms.
Exact Form:
y=-72
Decimal Form:
y=-3.5
Mixed Number Form:
y=-312
Solve for y 3*(-6y)=63

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top